Ritual and Tradition. Ceremonial in the Culture of Xochiojca, Veracruz (Urdimbre y Trama, Revista Mexicana de Religiosidad Popular, 2023)
In the community of Xochiojca, Veracruz, being a mayordomo is a privilege, since the stewardship of the patronal festival is the ritual space where the inhabitants practice the highest values that identify them as a people, it is where social capital is fostered and cultivated, but above all, it is where the inhabitants give meaning to community life by encountering the Divine. Throughout the months prior to the patronal festival, the mayordomos carry out various activities in favor of their position. For example, the attending general meetings of all the mayordomos that are held each month, where they are spiritually prepared for good performance. This makes clear the high level of his position, which denotes the seriousness and responsibility implicit in assuming this type of community deles. The responsibilities inherent in belonging to these organizational corporations continue throughout the year until reaching the culminating stage of this stewardship in the month of November, when from the first days of this month the preparations that involve the participation of the entire community.
Keywords: Xochiojca; mayordomia; cargo system; tradition; festival; saints; community